Healthful Plant-Based Dietary Patterns Associated with Reduced Adverse Effects of Air Pollution on COPD: Findings from a Large Cohort Study - Wang, Tianrun; Zhao, Chenyu; Fang, Xiaoqi; Zhao, Jia; Chao, Wangzhe; Bo, Yacong; Zhou, Liting (Nutrients, 2025)
Objectives: The potential of a plant-based diet (PD) to mitigate the adverse effects of long-term air pollution exposure on chronic obstructive pulmonary disease (COPD) remains uncertain. This study aims to explore both the independent and synergistic impacts of air pollution components and PD on COPD risk. Methods: Annual concentrations of air pollutants, including particulate matter (PM2.5, PM2.5–10, and PM10), as well as nitrogen oxides (NOX) and nitrogen dioxide (NO2), were estimated using a land-use regression model. We calculated the plant-based diet index (PDI), healthy plant-based diet index (hPDI), and unhealthy plant-based diet index (uPDI) by evaluating scores of 17 food categories. Cox regression was performed to evaluate their individual and combined effects on COPD risk. Results: This prospective cohort study included 162,741 participants. Every standard deviation increase in PM2.5, NO2, and NOX exposure was associated with an increased risk of COPD, with an adjusted HR (95% CI) of 1.049 (1.019, 1.079), 1.065 (1.034, 1.096), and 1.063 (1.035, 1.092), respectively. Compared with low-quality hPDI, moderate- and high-quality hPDI were associated with a lower risk of COPD with an adjusted HR (95% CI) of 0.884 (0.827, 0.946) and 0.758 (0.697, 0.825), respectively. For the combined effects, with the level of hPDI increasing, the joint effects of hPDI with PM2.5, NO2, and NOX showed a gradually increasing negative impact on COPD risk (p-interaction = 0.001, 0.005, and 0.005, respectively). Conclusions: Exposure to PM2.5, NO2, and NOx may elevate the risk of chronic obstructive pulmonary disease (COPD), whereas adherence to a high-quality hPDI could potentially counteract this association. Future research should explore the underlying biological mechanisms, assess the long-term effects of diet, and evaluate the effectiveness of dietary modifications in diverse populations to inform targeted prevention policies.